TINGKAT KEPUASAN PETERNAK AYAM BROILER TERHADAP POLA KEMITRAAN MODEL CONTRACT FARMING DI KECAMATAN KAMPAR KIRI TENGAH KABUPATEN KAMPAR (STUDY KASUS PT. PELITA TRIKENCANA BERSINAR) - Khairul Aswan; Cepriadi '; Kausar ' (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2016)
This study aims to determine the pattern of partnership is run by PT. Pelita Trikencana Bersinar, as well as to determine the level of satisfaction of plasma broiler breeders in partnership with PT. Pelita Trikencana Bersinar. This type of research is descriptive using quantitative and qualitative data, data collection through interviews with the help of questionnaires.The data analysis was use by descriptive method with Customer Satisfaction Index and Importance Satisfaction Index. The partnership that run is plasma with contract farming wihch the company as inti and the farmers as the plasma. The partnership betwen PT.Pelita Trikencana Bersinar and farmers is closed partnership wihch the farmer not have permission to sell the harvest or supply production input from the other company. PT. Pelita Trikencana Bersinar supply production input for plasma farmers in this fatnership, the farmers in the weakness position because the agreement given is standard rule that made by company. There are 7 variables that use he know Satisfaction Level of plasma farmers. The result shows that the value of Customer Satisfaction Index is 79,87 percent or 0,80 in range about 0,66-0,80. It meants that generally the satisfaction Index of plasma farmers be criteria Satisfied. From Importance Performance Analysis. Shows the variable that here lower performance the price of supply production input contract is expensive and supply production input quality not consistent in every period. Keywords: Broiler, ContractFarming, Partnership, Satisfaction